2022
DOI: 10.3390/plants11101310
|View full text |Cite
|
Sign up to set email alerts
|

Transcripts Expressed during Germination Sensu Stricto Are Associated with Vigor in Soybean Seeds

Abstract: The rapid and uniform establishment of crop plants in the field underpins food security through uniform mechanical crop harvesting. In order to achieve this, seeds with greater vigor should be used. Vigor is a component of physiological quality related to seed resilience. Despite this importance, there is little knowledge of the association between events at the molecular level and seed vigor. In this study, we investigated the relationship between gene expression during germination and seed vigor in soybean. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This is confirmed by studies on OGG1 in arabidopsis, where overexpression leads to reduced oxidative damage in dry and hydrated seeds [3]. Furthermore, in soybeans (Glycine max L.), it has been shown that an increase in OGG1 expression results in faster acquisition of germination and thus increased seed vigor [41]. The genes we studied could be used as molecular markers to predict seed quality in a very short time.…”
Section: Discussionsupporting
confidence: 67%
“…This is confirmed by studies on OGG1 in arabidopsis, where overexpression leads to reduced oxidative damage in dry and hydrated seeds [3]. Furthermore, in soybeans (Glycine max L.), it has been shown that an increase in OGG1 expression results in faster acquisition of germination and thus increased seed vigor [41]. The genes we studied could be used as molecular markers to predict seed quality in a very short time.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, from a seed physiology perspective, the difference in the above traits between seed lots was most likely due to different vigor levels caused by seed aging and deterioration [18]. From the start of seed imbibition to germination or emergence, metabolic repair, including DNA repair, is required and is a necessary step for the subsequent events leading to germination and emergence [55]. Low-vigor seeds germinate more slowly and with more difficulty due to a greater need for damage repair, especially under adverse environmental conditions, which ultimately causes different germination and emergence patterns between seed lots [56].…”
Section: Discussionmentioning
confidence: 99%
“…We previously selected target genes related to longevity and germination using the literature to perform the analysis. Based on the results of the literature analysis, we selected: HSFA3, HSP21, HSP17.6b [ 31 ], EXPA10 [ 32 ], and ABI3 [ 33 ]. The sequence of primers used are listed in Table 5 .…”
Section: Methodsmentioning
confidence: 99%